Students’ strategies of expanding fractions to a common denominator – a semiotic perspective - Lorange, Andreas; Rinvold, Reinert A. (NOMAD Nordic Studies in Mathematics Education, 2014)
The aim of this article is to identify students’ strategies while solving tasks which involve the expansion of fractions to a common denominator. In this case study we follow two groups of 11 year old students and their use of the artefact multilink cubes in the solution process. The analysis of the students’ strategies is based upon a semiotic-cultural framework. Five different types of strategies are reported: trial-and-error, factual, contextual, embodied-symbolic and symbolic. The concept of semiotic contraction is also used in the analysis.